2013
DOI: 10.1007/s10620-013-2747-1
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Bile Acid Synthesis, Metabolism and Excretion in a High Fat-Cholesterol Diet-Induced Fibrotic Steatohepatitis in Rats

Abstract: Background and AimsCholesterol over-intake is involved in the onset of nonalcoholic steatohepatitis (NASH), and hepatocellular bile acid (BA) accumulation correlates with liver injuries. However, how dietary cholesterol influences cholesterol and BA kinetics in NASH liver remains ambiguous and needs to be clarified.MethodsMolecular markers involved in cholesterol and BA kinetics were investigated at protein and mRNA levels in an already-established stroke-prone spontaneously hypertensive 5/Dmcr rat model with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Modification of hepatic bile acid metabolism and transporters[1214] and/or the gut microbiome[6,15] in NAFLD may alter the predominant bile acid species thereby impacting post-prandial bile acid-dependent signaling and modulating hepatic inflammatory cascades. Examination of bile acid species in patients currently abstinent from ethanol with steatohepatitis and cirrhosis revealed decreased secondary bile acids excreted in the stool and increased glycine- and taurine-conjugated bile acids in the serum.…”
Section: Introductionmentioning
confidence: 99%
“…Modification of hepatic bile acid metabolism and transporters[1214] and/or the gut microbiome[6,15] in NAFLD may alter the predominant bile acid species thereby impacting post-prandial bile acid-dependent signaling and modulating hepatic inflammatory cascades. Examination of bile acid species in patients currently abstinent from ethanol with steatohepatitis and cirrhosis revealed decreased secondary bile acids excreted in the stool and increased glycine- and taurine-conjugated bile acids in the serum.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the exception of Timp-1 mRNA, these increases were less in female rats than in males, especially at 14 weeks. 7 Previous studies showed that BA synthesis, export, and transformation are dysregulated in HFC-fed male rats [21], and these process have been associated with HFC-induced fibrogenesis [22]. HFC feeding significantly increased CYP7A1 protein levels at 8 and 14 weeks but decreased CYP8B1 (data not shown) protein expression in male and female rats at all time points in comparison with their respective controls (Figure 3).…”
mentioning
confidence: 67%
“…In a previous study, we established a fibrotic steatohepatitis model by feeding male stroke-prone spontaneously hypertensive rats (SHRSP5/Dmcr) with a high-fat-cholesterol (HFC) diet for 8 weeks, and demonstrated histopathological resemblance to human NASH [13,20]. We also showed that BAs and enzymes and promoters of BA kinetics play crucial roles in hepatic inflammation and fibrogenesis in this rat model [21][22][23]. Therefore, this model is likely appropriate for further investigations of the mechanisms behind gender differences in HFC-induced fibrotic steatohepatitis.…”
Section: Research Manuscript Sections 1 Introductionmentioning
confidence: 99%
“…Chemically induced models use direct hepatotoxic agents such as CCl 4 , dimethyl nitrosamine, and thioacetamide, which initiate hepatic inflammation, activating hepatic stellate cells. NAFLD cirrhosis may arise in mice fed with methionine‐deficient or choline‐deficient or a high‐fat diet. Bile duct ligation creates a mechanical obstruction of the bile duct, inducing cholestasis, cholangiocyte and hepatocyte injury, and fibrosis .…”
Section: Discussionmentioning
confidence: 99%